BRUSHY1/TONSOKU/MGOUN3 is required for heat stress memory. (12th July 2018) - Brzezinka, Krzysztof; Altmann, Simone; Bäurle, Isabel
Abstract: Plants encounter biotic and abiotic stresses many times during their life cycle and this limits their productivity. Moderate heat stress (HS) primes a plant to survive higher temperatures that are lethal in the naïve state. Once temperature stress subsides, the memory of the priming event is actively retained for several days preparing the plant to better cope with recurring HS. Recently, chromatin regulation at different levels has been implicated in HS memory. Here, we report that the chromatin protein BRUSHY1 ( BRU1 )/TONSOKU/MGOUN3 plays a role in the HS memory in Arabidopsis thaliana . BRU1 is also involved in transcriptional gene silencing and DNA damage repair. This corresponds with the functions of its mammalian orthologue TONSOKU‐LIKE/NFΚBIL2. During HS memory, BRU1 is required to maintain sustained induction of HS memory‐associated genes, whereas it is dispensable for the acquisition of thermotolerance. In summary, we report that BRU1 is required for HS memory in A. thaliana, and propose a model where BRU1 mediates the epigenetic inheritance of chromatin states across DNA replication and cell division. Abstract : Plants can be primed by a heat stress exposure to deal more efficiently with a future heat stress incident that occurs after a lag phase at normal growth temperatures. Studying the molecular basis of priming and memory in response to heat stress, we show here that the chromatin protein BRUSHY1 is required for heat stress memory and that it acts through sustaining the activation of heat stress‐memory related gene expression during the lag phase. Our findings suggest a model where heat stress memory is mediated through the epigenetic inheritance of chromatin states across cell divisions.